Mitochondrial dysfunction in pulmonary arterial hypertension - Zhang, Weiwei; Liu, Bo; Wang, Yazhou; Zhang, Hengli; He, Lang; Wang, Pan; Dong, Mingqing (Frontiers in Physiology, 2022)
Pulmonary arterial hypertension (PAH) is characterized by the increased pulmonary vascular resistance due to pulmonary vasoconstriction and vascular remodeling. PAH has high disability, high mortality and poor prognosis, which is becoming a more common global health issue. There is currently no drug that can permanently cure PAH patients. The pathogenesis of PAH is still not fully elucidated. However, the role of metabolic theory in the pathogenesis of PAH is becoming clearer, especially mitochondrial metabolism. With the deepening of mitochondrial researches in recent years, more and more studies have shown that the occurrence and development of PAH are closely related to mitochondrial dysfunction, including the tricarboxylic acid cycle, redox homeostasis, enhanced glycolysis, and increased reactive oxygen species production, calcium dysregulation, mitophagy, etc. This review will further elucidate the relationship between mitochondrial metabolism and pulmonary vasoconstriction and pulmonary vascular remodeling. It might be possible to explore more comprehensive and specific treatment strategies for PAH by understanding these mitochondrial metabolic mechanisms.